DEVELOPMENT OF GREEN BUILDING AND ECONOMIC STRATEGY - Urunbaev Saparbek Samatovich (Web of Journals Publishing, 2024)
The article discusses provides information on the benefits of green building construction, construction-related savings including increased employee productivity, reduced health and safety costs, and savings on energy, maintenance and operating costs.
Keywords: economy, sustainability, green buildings, green construction, climate change, green building strategy, energy, efficiency.